Assessment of the magnitude of behavioural risk factors among school going adolescents of Kashmir valley: a cross sectional study - Ali, Darakshan; Shah, Suhail; Nazir, Muzamil; Fazili, Anjum B. (International Journal Of Community Medicine And Public Health, 2023)
Background: Adolescents are one sixth of the world’s population and account for 6% of the global burden of disease and injury. The unique health issues associated with adolescence have been little understood. Adolescence is a period when many behaviours are consolidated which have major effects on future adult health. Methods: A cross sectional study was conducted in a total of 8 schools in order to assess the magnitude of various behavioural risk factors among school going adolescents. 614 students in the age group of 10-19 years were included in the study. Data was collected using modified WHO global school-based health survey questionnaire. Weight and height of the adolescents were also taken to assess their nutritional status. Results: In the present study 45% of the participants resorted to diet restriction. 19.2% of the adolescents felt lonely. 18.2.5% of the participants had disturbed sleep and 8.8% of them reported having had suicidal thoughts. 3.9% of the participants had ever smoked cigarettes, 3.9% had ever consumed alcohol and 1.8% had ever used drugs. 28.3% of the adolescents reported having been physically attacked and 12.5% reported having been bullied. 29.5% had a screen time of 3 hours or more. Conclusions: It was observed that behavioral risk factors like unhealthy eating habits and lack of physical activity and substance abuse were quite prevalent in the adolescents. Health education on all these behavioural risk factors and incorporation of life skills education in the school curriculum will help in improving the overall health of the adolescents.